О ГРАНИЧНЫХ УСЛОВИЯХ ДЛЯ НАПРЯЖЕННОСТИ ЭЛЕКТРИЧЕСКОГО ПОЛЯ НА ПОВЕРХНОСТИ ДВИЖУЩЕГОСЯ ПРОВОДЯЩЕГО ТЕЛА - Михайлов , В.М. (Інститут електродинаміки НАН України, Київ, 2023)
Boundary conditions for electric field strength on border of moving conductor and moveless nonconductive continuum are obtained. Examples of using its in the problem of magnetic field penetration into moving conductor are presented. It’s shown that using of effective or usual electric field strength has not an influence on form of boundary condition for magnetic field strength in moveless coordinates. References 8, figures 2.